HASIL BELAJAR GERAK DASAR SENAM LANTAI: STUDI TENTANG HUBUNGAN CAPAIAN KOGNITIF DAN PSIKOMOTOR SISWA MATA PELAJARAN PJOK - I'tamada, Eldiene Zaura; Hayati, Hayati; Supriyanto, Supriyanto (Gelanggang Pendidikan Jasmani Indonesia, 2024)
This study was conducted to determine the relationship between knowledge scores and basic gymnastics floor movement skills in phase-E high school students conducted at SMA Negeri 1 Gedangan, Sidoarjo with a total of 109 students. The method used in this study was a comparative survey that compared the results of movement skills and knowledge scores described through a descriptive quantitative approach and correlation analysis conducted using Microsoft Excel and SPSS type 25. The results of the data correlation showed that there was no relationship between skills and students' knowledge of the learning material with a significance value of 0.092 because 56% of students had better skill scores than knowledge scores. Students who had skill and knowledge scores with the same category only 31 students so that the learning process requires interactive teaching materials in order to improve students' knowledge related to the learning material.